Entrenamiento en habilidades de autocontrol con técnicas cognitivo conductuales en niños y niñas de 8 a 11 años de la fundación "Niños con Destino" del Valle de los Chillos - Cañizares Mejía, Karen Lorena (2016)
It has carried out a clinical intervention in children of 8-11 years of the Foundation Niños con Destino, located in Valle de los Chillos, Sangolquí Ecuador, focused to the training in self-management skills with cognitive behavioral techniques such as: the self-instructions of Meichenbaum, Token Economy, Autogenic training of Shultz and Social Skills training of Goldstein, among others. These children showed aggressive behaviors in the development of daily activities and low social skills development, opposed to aggression, such skills related with emotions and feelings and assertiveness. Has been made a program aimed at promoting the development of new behavior in children to enable them to develop in more adaptive way in their environment; the intervention is divided into two stages: pretreatment evaluation in which through psychometric tests such as The Matson Evaluation of Social Skills with Youngsters MESSY (Matson, Rotatori & Helsel, 1983) and the social interaction skill questionnaire CHIS (Monjas, 1994), the group was selected to be intervened and the post treatment in which these tests are applied in order to statistically compare results; systematization also consists of the experience gained during the implementation of the training program highlighting successes, failures, alternatives to be used in future similar interventions and factors that suggest a change in the policies of the organization of the institution.